Soil organic matter interactions along the elevation gradient of the James Ross Island (Antarctica) - V. Vlček; D. Juřička; M. Valtera; H. Dvořáčková; V. Štulc; M. Bednaříková; J. Šimečková; P. Váczi; M. Pohanka; P. Kapler; M. Barták; V. Enev (SOIL, 2024)
Around half of the Earth's soil organic carbon (SOC) is presently stored in the Northern Hemisphere permafrost region. In polar permafrost regions, low temperatures particularly inhibit both the production and biodegradation of organic matter. Under such conditions, abiotic factors such as mesoclimate, pedogenic substrate or altitude are thought to be more important for soil development than biological factors. In Antarctica, biological factors are generally underestimated in soil development due to the rare occurrence of higher plants and the short time since deglaciation. In this study, we aim to assess the relationship between SOC and other soil properties related to the pedogenic factors or properties. Nine plots were investigated along the altitudinal gradient from 10 to 320 m in the deglaciated area of James Ross Island (Ulu Peninsula) using a parallel tea-bag decomposition experiment. SOC contents showed a positive correlation with the content of easily extractable glomalin-related soil protein (EE-GRSP; Spearman r =0.733 , P =0.031 ) and the soil buffering capacity (expressed as Δ pH; Spearman r =0.817 , P =0.011 ). The soil-available P was negatively correlated with altitude (Spearman r = - 0.711 <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="55pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="7148a909bb34bdb2df1009de6e6c5689"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="soil-10-813-2024-ie00001.svg" width="55pt" height="10pt" src="soil-10-813-2024-ie00001.png"/></svg:svg> , P =0.032 ), and the exchangeable Mg was negatively correlated with the rock fragment content (Spearman r = - 0.683 <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="55pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="367107d415f8d56a3622e3ec206d61c1"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="soil-10-813-2024-ie00002.svg" width="55pt" height="10pt" src="soil-10-813-2024-ie00002.png"/></svg:svg> , P =0.050 ). No ...